Juridical Analysis of Insurance Agreements According to Civil Code and Insurance Law - Nur Asiyah Siregar; Ernawati; Hahir Siregar; Dimas Agung Nugroho (ISNU Sumatera Utara, 2026)
Insurance agreements are a form of agreement that has special characteristics because it involves elements of risk transfer between the insurer and the insured. This research aims to analyze juridically insurance agreements according to the Civil Code (KUH-Percivil) and Law Number 40 of 2014 concerning Insurance. The research method used is normative legal research with a statutory approach and a conceptual approach. The data used are sourced from primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that insurance agreements according to the Civil Code are subject to the general provisions of the agreement as stipulated in Article 1320 of the Civil Code, as well as special provisions in the Commercial Law Code (KUHD). Meanwhile, the Insurance Law provides more comprehensive arrangements related to legal protection for parties, the principle of prudence, and supervision of insurance companies. Thus, insurance agreements must not only meet the legal requirements of the agreement according to the Civil Code, but also must comply with special provisions in the Insurance Law to ensure legal certainty and protection for the insured.